(untitled) (Perner’s Contacts, 2019)
Paper introduces the basic approach to development International Standard in the area of conceptual and logical data model and physical encoding format for geographic databases for Intelligent Transport Systems (ITS) applications and services. The focus is on Cooperative-ITS services and automated driving systems, and relevant information about road lanes.